The Efficacy and Safety of Antipsychotic Medications in the Treatment of Psychosis in Patients with Parkinson’s Disease - Nevena Divac; Radan Stojanović; Katarina Savić Vujović; Branislava Medić; Aleksandar Damjanović; Milica Prostran (Behavioural Neurology, 2016)
Psychotic symptoms are present in up to 50% of patients with Parkinson’s disease. These symptoms have detrimental effects on patients’ and caregivers’ quality of life and may predict mortality. The pathogenesis of psychotic symptoms in Parkinson’s disease is complex, but the use of dopaminergic medications is one of the risk factors. The treatment of psychotic symptoms in Parkinson’s disease is complicated due to the ability of antipsychotic medications to worsen motor symptoms. The efficacy of clozapine in the treatment of psychosis in patients with Parkinson’s disease has been confirmed in several clinical trials; however, the adverse effects and the necessity of blood count monitoring are the reasons why the use of this drug is challenging. The studies on safety and efficacy of other antipsychotics conflicting results. The use of antipsychotics in these patients is also associated with increased mortality. Psychotic symptoms in Parkinson’s disease per se are also proven predictors of mortality. Thus it is necessary to treat psychotic symptoms but the choice of an antipsychotic should be based on careful risk/benefit assessment. Pimavanserin as a novel therapeutic option with more favorable adverse effects profile is now available for this indication, but careful postmarketing monitoring is necessary to establish the true picture of this drug’s long-term safety and efficacy.